Dietary intake of calcium and postmenopausal bone loss. Issue 6640 (2nd July 1988) - Stevenson, J. C.; Whitehead, M. I.; Padwick, M.; Endacott, J. A.; Sutton, C.; Banks, L. M.; Freemantle, C.; Spinks, T. J.; Hesp, R.
Abstract : The use of calcium supplements to prevent postmenopausal bone loss and hence osteoporosis is widespread, but the evidence for their efficacy, either alone or in combination with other treatments, is contradictory. Skeletal measurements and dietary intake of calcium were determined in 59 healthy postmenopausal women, most of whom were within five years of the menopause. No correlation was found between current intake of calcium and either total calcium in the body or the density of trabecular or cortical bone in the forearm or vertebral trabecular bone. Dietary intake of calcium did not influence the rate of postmenopausal bone loss in the 54 women who completed 12 months of active or placebo treatment. Even when extremes of calcium intake were examined no difference was found in bone measurements between the women with the highest and lowest intakes. The results of this study suggest that the bone density of women in the early menopause is not influenced by current dietary intake of calcium.